1998
DOI: 10.1097/00000372-199802000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic and Immunohistochemical Features in Human Skin after Exposure to Nitrogen and Sulfur Mustard

Abstract: N-methyl-2,2'-dichlorodiethylamine (HN2)is a topical chemotherapeutic agent used as therapy for cutaneous T-cell lymphomas (CTCL). Di(2-chloroethyl)sulfide (SM), and less often HN2, have been used as chemical weapons, with the skin being a principle target. The mechanisms by which these chemicals produce their therapeutic and toxic effects in skin, however, are not clearly defined. We exposed human skin explants to two doses of HN2 and SM. At 18 hours after exposure, histopathologic features were compared. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
65
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 11 publications
6
65
0
Order By: Relevance
“…Dual function transcription factors have been described that switch their function by interaction with different co-activators or co-repressors (40 -42), different neighboring transacting factors (43)(44)(45), or interaction with specific DNA sequences in different locations relative to the transcription start site (46). MDBP/RFX interacts with c-Abl, greatly stimulating its autophosphorylation (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dual function transcription factors have been described that switch their function by interaction with different co-activators or co-repressors (40 -42), different neighboring transacting factors (43)(44)(45), or interaction with specific DNA sequences in different locations relative to the transcription start site (46). MDBP/RFX interacts with c-Abl, greatly stimulating its autophosphorylation (47).…”
Section: Discussionmentioning
confidence: 99%
“…The data presented here indicate that MDBP/RFX behaves as transcriptional repressor in the context of methylated collagen ␣2(I) sequence. We have previously demonstrated that in a rat cell line that has lost expression of this gene, there is methylation in the promoter region and that treatment of this cell line with the DNA demethylating agent 5-azacytidine results in the gain of expression of this gene (43). Because abnormal hypermethylation of the 5Ј region of tumor suppressor genes is so frequent in cancer and down-regulation of collagen gene expression has been proposed to contribute to carcinogenesis, abnormal methylation of the 5Ј region of the ␣2(I) gene, including the MDBP/RFX site, might occur in cancers and play a role in down-regulation of the expression of this gene.…”
Section: Discussionmentioning
confidence: 99%
“…Sulfur mustard (bis(2-chloroethyl)sulfide, HD) is a chemical warfare agent that penetrates the skin rapidly and causes extensive blistering after a latent period of several hours (1)(2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…This study is divided into two sections: (1) a time course study and (2) a compound evaluation study. The specific aim of the time course study was to determine whether MMP and MMP substrate gene expression levels are altered over time (6,12,24, and 72 h) in mouse ear skin topically exposed to liquid HD. Gene expression profiles support the identification of specific targets for therapeutic countermeasures against HD-induced skin injury and provide additional biochemical markers for understanding HD toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Yet at this time, no single drug or combination of known protective agents appear to afford enough protection to be considered a sulfur mustard therapeutic agent (10).…”
Section: Introductionmentioning
confidence: 99%